Ancient Wisdom for Modern Stress: Integrating IKS in Education for Mental Wellbeing - Kumari, Annu; Sharma, Jobasmita; Rabha, Sikha; Shangpliang, P. Wankitlang (Journal of Neonatal Surgery, 2025)
Over the course of millennia, the Indian subcontinent has produced a huge, multidisciplinary corpus of classical and traditional knowledge known as Indian Knowledge Systems (IKS). These systems combine scientific, philosophical, artistic, and spiritual perspectives to provide a comprehensive understanding of life, the cosmos, and human existence.In order to promote cognitive development, cultural identity, mental health, and sustainable living, this research examines the application and significance of IKS in modern higher education.Key elements including the Vedic mathematical tradition, classical arts, Ayurveda, and yoga are highlighted, and via empirical research and policy analysis, their educational and therapeutic benefits are demonstrated.Institutional frameworks and knowledge repositories are examined, as well as how IKS might be incorporated into postsecondary institutions through faculty training, curricular reform, and digital preservation. Critical analysis is done on issues including overcoming infrastructure constraints, avoiding dogmatism, and guaranteeing educational inclusion. The paper concludes by arguing that a careful incorporation of IKS into contemporary education can close the knowledge gap between ancient and modern wisdom, providing students with a more comprehensive, inclusive, and value-based educational experience.